Single-cell sequencing elucidates the mechanism of NUSAP1 in glioma and its diagnostic and prognostic significance - Zhao, Meng-Yu; Shen, Zhao-Lei; Dai, Hongzhen; Xu, Wan-Yan; Wang, Li-Na; Gu, Yu-; Zhao, Jie-Hui; Yu, Tian-Hang; Wang, Cun-Zhi; Xu, Jia-feng; Chen, Guan-Jun; Chen, Dong-Hui; et al. (Frontiers in Immunology, 2025)
BackgroundPersonalized precision medicine (PPPM) in cancer immunology and oncology is a rapidly advancing field with significant potential. Gliomas, known for their poor prognosis, rank among the most lethal brain tumors. Despite advancements, there remains a critical need for precise, individualized treatment strategies.MethodsWe conducted a comprehensive analysis of RNA-seq and microarray data from the TCGA and GEO databases, supplemented by single-cell RNA sequencing (scRNA-seq) data from glioma patients. By integrating single-cell sequencing analysis with foundational experiments, we investigated the molecular variations and cellular interactions within neural glioma cell subpopulations during tumor progression.ResultsOur single-cell sequencing analysis revealed distinct gene expression patterns across glioma cell subpopulations. Notably, differentiation trajectory analysis identified NUSAP1 as a key marker for the terminal subpopulation. We found that elevated NUSAP1 expression correlated with poor prognosis, prompting further investigation of its functional role through both cellular and animal studies.ConclusionsNUSAP1-based risk models hold potential as predictive and therapeutic tools for personalized glioma treatment. In-depth exploration of NUSAP1’s mechanisms in glioblastoma could enhance our understanding of its response to immunotherapy, suggesting that targeting NUSAP1 may offer therapeutic benefits for glioma patients.